2003
DOI: 10.1167/iovs.02-1317
|View full text |Cite
|
Sign up to set email alerts
|

Water Permeability of C-Terminally Truncated Aquaporin 0 (AQP0 1-243) Observed in the Aging Human Lens

Abstract: These data provide evidence that loss of 20 amino acids from the C terminus may not directly affect the ability of AQP0 to transport water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 66 publications
(58 reference statements)
2
61
2
Order By: Relevance
“…These conductance characteristics are not changed by proteolytic cleavage of AQP0 24 . As our structure, obtained with the double-layered 2D crystals grown at pH 6 7 , reveals fewer water molecules in the pore than the structure determined from the 3D crystals grown at pH 10.5 8 , pore closure appears to be a result of junction formation, not pH shift.…”
Section: Water Molecules In the Aqp0 Porementioning
confidence: 86%
“…These conductance characteristics are not changed by proteolytic cleavage of AQP0 24 . As our structure, obtained with the double-layered 2D crystals grown at pH 6 7 , reveals fewer water molecules in the pore than the structure determined from the 3D crystals grown at pH 10.5 8 , pore closure appears to be a result of junction formation, not pH shift.…”
Section: Water Molecules In the Aqp0 Porementioning
confidence: 86%
“…13 Treatment of AQP0 with proteolytic enzymes generates more junctional AQP0 13 and structural characterization suggests the truncated junctional form has a closed water pore. 49 However, functional studies demonstrated equal permeability of full-length and truncated AQP0, 11,50 and showed full-length AQP0 has adhesive properties. 12 Another possible consequence of Cterminal truncation is that key residues involved in AQP0 protein-protein interactions are removed.…”
Section: Discussionmentioning
confidence: 99%
“…The discovery of AQP1 as a water channel in RBCs by Peter Agre's lab (Preston et al, 1994) suggested the closely related AQP0 might also be a water channel. Subsequent in vitro expression of AQP0 in Xenopus oocytes showed that AQP0 does function as a water channel (Kushmerick et al, 1995;Mulders et al, 1995;Chandy et al, 1997;Francis et al, 2000a,b;Schey et al, 2000;Chepelinsky, 2003;Ball et al, 2003) and possibly also as a glycerol transporter (Kushmerick et al, 1998). Varadaraj et al (1999Varadaraj et al ( , 2005 investigated the function of AQP0 in the mammalian lens and corroborated its role as a water transporter but found no evidence for glycerol transport.…”
Section: Introductionmentioning
confidence: 99%